2015
DOI: 10.4103/0028-3886.156277
|View full text |Cite
|
Sign up to set email alerts
|

Decompressive craniectomy in traumatic brain injury: A single-center, multivariate analysis of 1,236 patients at a tertiary care hospital in India

Abstract: The severity of head injury, performing a duraplasty rather than a slit durotomy, avoidance of a contralateral DC, and the presence of preoperative hypotension, infarct, and/or pupillary asymmetry have the highest odds of predicting the short term GOS at the time of discharge, after a DC in patients with TBI. Although DC carries a high risk of mortality, the probability of the survivors having a favorable outcome is significantly more as compared to those who remain in a PVS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 24 publications
(38 reference statements)
2
28
0
Order By: Relevance
“…The relative increase in the use of this procedure and the improvement in the survival rate have led to a growing number of patients who might need a cranioplasty. [1][2][3][4][5] Classically, the benefits of a cranioplasty were primarily to protect the brain and repair cosmetic defects. However, there are an increasing number of publications suggesting that cranioplasties may result in neurological improvement via increased cerebral blood flow (CBF), and an improvement of cerebrospinal fluid (CSF) dynamics and cerebral metabolism.…”
mentioning
confidence: 99%
“…The relative increase in the use of this procedure and the improvement in the survival rate have led to a growing number of patients who might need a cranioplasty. [1][2][3][4][5] Classically, the benefits of a cranioplasty were primarily to protect the brain and repair cosmetic defects. However, there are an increasing number of publications suggesting that cranioplasties may result in neurological improvement via increased cerebral blood flow (CBF), and an improvement of cerebrospinal fluid (CSF) dynamics and cerebral metabolism.…”
mentioning
confidence: 99%
“…12 In our study, it is found that male to female ratio was 3.8:1 with 79.46% males and 20.53% females and it is also comparable to other studies. 6,[13][14][15] Males in the age group of 19 to 40 years are more affected than females with a ratio of Abbreviation: CSF, cerebrospinal fluid; PCA, posterior cerebral artery; MCA, middle cerebral artery.…”
Section: Discussionmentioning
confidence: 99%
“…Low and middle income countries like India constitute 90% of the burden of traumatic brain injury (TBI). Without insurance or state sponsored specialised care, the cost of the treatment is borne by the patient's family (5).…”
mentioning
confidence: 99%